Posthumanist and New Materialist Perspectives as Navigational Tool in Art Education Research: A Diffractive Analysis - Kotze, Roline; Perold-Bull, Karolien; Costandius, Elmarie; Alexander, Neeske (Critical Studies in Teaching and Learning, 2023)
An art project conducted with twelve Grade 10 learners at an art centre in Cape Town from April 2016 to June 2016 was analysed diffractively using perspectives of posthumanism and new materialism. This post-qualitative approach to research was an attempt to move away from research methods based on humanist thinking. Data consisted of the art project, learners’ responses in terms of source book content and work produced, informal discussions, and videos and photographs taken during the work processes. Several specific agential cuts were performed on the data, some of which are presented here. The analysis of these entanglements of data provided rich content and interesting lines of flight, which led to thought-provoking questions about art education, sensory education, and the possibilities of applying posthumanist thought and methods in the South African art classroom.